High-Precision Remote Sensing Monitoring of Extent, Species, and Production of Cultured Seaweed for Korean Peninsula - Shuangshuang Chen; Zhanjiang Ye; Runjie Jin; Junjie Zhu; Nan Wang; Yuhan Zheng; Junyu He; Jiaping Wu (Remote Sensing)
Sustainable seaweed cultivation is crucial for marine environmental protection, ecosystem health, socio-economic development, and carbon sequestration. Accurate and timely information on the distribution, extent, species, and production of cultivated seaweeds is essential for tracking biomass production, monitoring ecosystem health, assessing environmental impacts, optimizing cultivation planning, supporting investment decisions, and quantifying carbon sequestration potential. However, this important information is usually lacking. This study developed a high-precision monitoring approach by integrating Otsu thresholding features with random forest classification, implemented through Google Earth Engine using Sentinel-2 imagery (10-m). The method was applied to analyze spatiotemporal variations of seaweed cultivation across the Korean Peninsula from 2017 to 2023. Results showed that annual cultivation acreage in North Korea remained relatively stable between 1506 and 2033 ha, while it experienced a significant increase of 8209 ha in South Korea. By integrating spectral features, seaweed phenology, and field cultivation practices, we successfully differentiated the predominant species: laver (Pyropia) and kelp (Saccharina and Undaria). During the 2022–2023 cultivation season, South Korea’s farms comprised 78% laver and 22% kelp, while North Korea’s showed an inverse distribution. A strong correlation (r2 = 0.99) between acreage and seaweed production enabled us to estimate annual seaweed production in North Korea, effectively addressing data gaps in regions with limited statistics. Our approach demonstrates the potential for global seaweed cultivation monitoring, while the spatial analysis lays the foundation for identifying potential cultivation zones. Given the relatively low initial investment requirement of seaweed farming and significant economic return, this approach offers valuable insights for promoting economic development and food security, ultimately supporting sustainable aquaculture management.